2014
DOI: 10.4103/0972-5229.130573
|View full text |Cite
|
Sign up to set email alerts
|

Scoring systems in the intensive care unit: A compendium

Abstract: Severity scales are important adjuncts of treatment in the intensive care unit (ICU) in order to predict patient outcome, comparing quality-of-care and stratification for clinical trials. Even though disease severity scores are not the key elements of treatment, they are however, an essential part of improvement in clinical decisions and in identifying patients with unexpected outcomes. Prediction models do face many challenges, but, proper application of these models helps in decision making at the right time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 46 publications
1
136
0
11
Order By: Relevance
“…Therefore, further studies are required to determine whether COPD reduces weaning success in patients requiring PMV. The SOFA scoring system, which was introduced in 1994, is a reliable predictive factor of mortality during ICU stay (28). Gnanapandithan et al reported that the value of the baseline SOFA scores at baseline was related to successful extubation from MV (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are required to determine whether COPD reduces weaning success in patients requiring PMV. The SOFA scoring system, which was introduced in 1994, is a reliable predictive factor of mortality during ICU stay (28). Gnanapandithan et al reported that the value of the baseline SOFA scores at baseline was related to successful extubation from MV (29).…”
Section: Discussionmentioning
confidence: 99%
“…These prognoses may be useful in estimating patient's physiologic in- (46) stability upon admission (46). In addition, severity scoring and forecasting mortality for each patient can be performed along with clinical assessment in the ICU in order to increase chances of survival (47,48). Based on the findings of the current study, there was a positive significant association between APACHE-II score, renal damage, mortality, and ICU duration.…”
Section: Discussionmentioning
confidence: 64%
“…Hospital mortality is predicted using the APACHE II score, the principal diagnostic category with which the patient is admitted to ICU and also depending on whether or not the patient required emergency surgery. [12] In a recent study, APACHE II has also had a better, more appropriate calibration than other widely used scoring systems; so only APACHE II properly predicts mortality risk. [11] The major limitation of this scoring system is the varibility of physiological parameters which are all dynamic and can be influenced by multiple factors, including ongoing resuscitation and treatment, hence, time bias is present.…”
Section: Discussionmentioning
confidence: 99%